FINANCIAL REPORTING: STUDY PADA UMKM DI KABUPATEN NGANJUK - Dekrijanti, Indra; Lutfi, Mohammad Ali (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study was to describe the financial reporting of MSMEs in Nganjuk Regency and to obtain the suitability of accounting/finance reporting for Micro, Small and Medium Enterprises in Nganjuk Regency through EMKM Accounting Standards. The research method used is based on qualitative descriptive analysis, besides that the researcher also uses source triangulation and source triangulation methods. The results of this study indicate that the financial disclosure of MSMEs in Nganjuk Regency has not implemented SAK ETAP. Financial condition reports are still limited to cash disbursements and inflows, have not implemented monetary position affirmations, payment articulations and fiscal report notes.